Headgear use in girls’ lacrosse—stakeholders not ready for change - Recker, Robyn; Myers, Alison; Desai, Nikhil; Caccese, Jaclyn B.; Boucher, Laura; Onate, James; Yang, Jingzhen (Frontiers in Sports and Active Living, 2024)
Purpose Mandating headgear for field players in girls’ lacrosse to reduce head injuries, including concussion, has been heavily debated. However, research regarding the need and effectiveness of mandated headgear use in girls’ lacrosse is still developing. Therefore, this qualitative study aimed to identify the need for and barriers to the development of mandated headgear use policies in girls’ lacrosse in Ohio. Methods We conducted six virtual focus groups, three with concussion experts (clinicians and researchers) and three with girls’ lacrosse stakeholders (high school players, parents, coaches, and officials). A focus group guide was developed to explore study participants’ perceptions and opinions on concussion in girls’ lacrosse, headgear use among players, and policies and policy development related to headgear use or a headgear mandate. We developed the codebook using an inductive and iterative approach based on focus group transcripts and used ATLAS.TI to code and analyze the transcript data. Results Concussion experts and stakeholders understood the potential consequences of concussion but did not perceive concussion as a pervasive problem in girls’ lacrosse. The prevention of head and facial injuries was regarded as a potential benefit of headgear use. However, stakeholders expressed that the myriad of arguments discussed opposing mandated headgear use including increased aggressive play and/or targeting, concerns over changes in the game, and cost strongly outweighed the benefits. Finally, both concussion experts and stakeholders identified multiple organizations, including USA Lacrosse, who could act as facilitators and/or barriers to developing, enacting, and implementing headgear policies. Conclusions Concussion experts and stakeholders identified possible reasons for headgear use related to injury prevention but also identified several important barriers to the development of a headgear mandate for girls’ lacrosse in Ohio.